Ancestry-informative markers on chromosomes 2, 8 and 15 are associated with insulin-related traits in a racially diverse sample of children - Klimentidis Yann C (Human Genomics, 2011)
Abstract Type 2 diabetes represents an increasing health burden. Its prevalence is rising among younger age groups and differs among racial/ethnic groups. Little is known about its genetic basis, including whether there is a genetic basis for racial/ethnic disparities. We examined a multi-ethnic sample of 253 healthy children to evaluate associations between insulin-related phenotypes and 142 ancestry-informative markers (AIMs), while adjusting for sex, age, Tanner stage, genetic admixture, total body fat, height and socio-economic status. We also evaluated the effect of measurement errors in the estimation of the individual ancestry proportions on the regression results. We found that European genetic admixture is positively associated with insulin sensitivity (SI), and negatively associated with the acute insulin response to glucose, fasting insulin levels and the homeostasis model assessment of insulin resistance. Our analysis revealed associations between individual AIMs on chromosomes 2, 8 and 15 and these phenotypes. Most notably, marker rs3287 at chromosome 2p21 was found to be associated with SI (p = 5.8 × 10-5). This marker may be in admixture linkage disequilibrium with nearby loci (THADA and BCL11A) that previously have been reported to be associated with diabetes and diabetes-related phenotypes in several genome-wide association and linkage studies. Our results provide further evidence that variation in the 2p21 region containing THADA and BCL11A is associated with type 2 diabetes. Importantly, we have implicated this region in the early development of diabetes-related phenotypes, and in the genetic aetiology of population differences in these phenotypes.